2013
DOI: 10.1037/a0034740
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing 2,260 opinions of defendants’ restorability to adjudicative competency.

Abstract: We examined 2,260 forensic assessments in which the evaluator opined that the defendant was incompetent to stand trial. In approximately one half of these evaluations (52%), the evaluator concluded that the defendant was likely to be restored to competency in the foreseeable future. This opinion was reached more frequently with defendants who were female, under the age of 60, suffering from an affective or psychotic disorder with previous psychiatric hospitalizations, and who were noncompliant with psychiatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 22 publications
4
25
1
Order By: Relevance
“…Such statistics highlight the significant demand for competency restoration services. Despite this demand, the study of competency restoration treatment remains an empirically underdeveloped concept (Warren, Chauhan, Kois, Dibble, & Knighton, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such statistics highlight the significant demand for competency restoration services. Despite this demand, the study of competency restoration treatment remains an empirically underdeveloped concept (Warren, Chauhan, Kois, Dibble, & Knighton, ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous research (Advokat et al ., ; Colwell & Gianesini, ; Cooper & Zapf, ; Hubbard et al ., ; Jacobs, Ryba, & Zapf, ; Morris & DeYoung, ; Morris & Parker, , ; Mossman, ; Warren et al ., ), we propose the following hypotheses: (1) A greater number of psychotic (e.g., delusions, paranoia, derailment, constricted affect, auditory hallucinations, and visual hallucinations) and neuropsychological (e.g., perseveration, impaired orientation, impaired executive functioning, stroke, memory problems, stereotyped movements, impaired attention, seizures, aphasia, echolalia, apraxia, and agnosia) symptoms will predict both IST and competency non‐restoration; (2) severe cognitive symptoms (e.g., lack of orientation, executive functioning deficits, derailment) will be associated with initial IST opinions and non‐restoration; (3) depressive (e.g., indecisiveness, fatigue, hopelessness, decrease/increase in appetite, depressed mood, impaired hygiene, suicidal ideation, decrease/increase in sleep, guilt, and motor retardation), anxiety (e.g., avoidance, increased heart rate, chest discomfort, dizziness, repetitive behaviour, sweating, fear of going crazy, worry, fear, shaking, hypervigilance, fear of social situations, fear of dying, shortness of breath, nausea, chills, and repetitive mental acts), manic (e.g., tangential speech, motor hyperactivity, flight of ideas, pressured speech, distractibility, irritability, and grandiosity), and/or Cluster B personality disorder symptoms (e.g., manipulative, lacks remorse, malingering, uncooperative, entitled, seductive, grandiose) will not be related to IST or non‐restoration; and (4) older age will predict IST and non‐restoration.…”
Section: Introductionmentioning
confidence: 99%
“…Medication refusal . The research literature shows that compliance with psychiatric medications is associated with better restoration outcomes (e.g., Galin, Wallerstein, & Miller, 2016; McMahon, Marioni, Lilly, & Lape, 2014; Warren et al., 2013). Not surprisingly, this study found that those refusing medications had a very low rate of restoration (only 30%), as compared with those with intermittent compliance (48%), full adherence (62%) and who were not prescribed medications (70%).…”
Section: Discussionmentioning
confidence: 99%
“…25 Courts order an estimated 25,634-51,500 CST evaluations each year nationally, varying from fewer than 50 to approximately 5,000 per year in individual states. 26,27 Numbers of evaluations continue to increase annually. For example, CST evaluations in Wisconsin increased 32.5% from 2010 through 2015, 28 while evaluations in Washington increased 76.3% from 2001 through 2012.…”
Section: Efficiencymentioning
confidence: 99%